Plasma tau complements CSF tau and P-tau in the diagnosis of Alzheimer's disease - Fossati, Silvia; Ramos Cejudo, Jaime; Debure, Ludovic; Pirraglia, Elizabeth; Sone, Je Yeong; Li, Yi; Chen, Jingyun; Butler, Tracy; Zetterberg, Henrik; Blennow, Kaj; de Leon, Mony J. (Alzheimer's & dementia : diagnosis, assessment & disease monitoring, 2019)
Plasma tau may be an accessible biomarker for Alzheimer's disease (AD), but the correlation between plasma and cerebrospinal fluid (CSF) tau and the value of combining plasma tau with CSF tau and phospho-tau (P-tau) are still unclear. Plasma-tau, CSF-tau, and P-tau were measured in 97 subjects, including elderly cognitively normal controls (n = 68) and patients with AD (n = 29) recruited at the NYU Center for Brain Health, with comprehensive neuropsychological and magnetic resonance imaging evaluations. Plasma tau was higher in patients with AD than cognitively normal controls (P < .001, area under the receiver operating characteristic curve = 0.79) similarly to CSF tau and CSF P-tau and was negatively correlated with cognition in AD. Plasma and CSF tau measures were poorly correlated. Adding plasma tau to CSF tau or CSF P-tau significantly increased the areas under the receiver operating characteristic curve from 0.80 and 0.82 to 0.87 and 0.88, respectively. Plasma tau is higher in AD independently from CSF-tau. Importantly, adding plasma tau to CSF tau or P-tau improves diagnostic accuracy, suggesting that plasma tau may represent a useful biomarker for AD, especially when added to CSF tau measures. •Both plasma- and CSF-tau are elevated in patients with AD recruited at the NYU Center for Brain Health.•Plasma tau is correlated with cognition, but not with CSF tau, in AD.•Plasma tau increases diagnostic accuracy (AUC) when added to CSF-tau or P-tau.•SIMOA and ELISA assays performed in the same CSF samples are strongly correlated.•Plasma- and CSF-tau measures appear complementary. The reasons warrant further investigation.